Treatment Regimens with Bypassing Agents in Patients with Hemophilia A and Inhibitors: A Survey from the Italian Association of Hemophilia Centers (AICE) - Coppola, Antonio; Franchini, Massimo; Castaman, Giancarlo; Santagostino, Elena; Santoro, Cristina; Santoro, Rita Carlotta; Morfini, Massimo; Di Minno, Giovanni; Rocino, Angiola; on behalf of the AICE ad hoc Working Group (Seminars in Thrombosis and Hemostasis, 2018)
The development of neutralizing antibodies (inhibitors) against infused factor VIII currently represents the main complication of replacement therapy in patients with severe hemophilia A. Inhibitors, indeed, particularly high-titer inhibitors (>5 BU/mL), greatly complicate the management of bleeding, exposing patients to an increased morbidity and mortality risk, thus representing a significant burden for physicians of Hemophilia Treatment Centers (HTCs). Although bypassing agents (i.e., activated prothrombin complex concentrate [APCC] and recombinant activated factor VII [rFVIIa]) are available for the treatment and prevention of bleeding in inhibitor patients, their efficacy, safety, and cost–benefit outcomes are poorly known in the long term and should be further improved. In the frame of the update of recommendations for the management of inhibitor patients by the Italian Association of Hemophilia Centers (AICE), to collect more information on real-life therapeutic approaches with bypassing agents in this setting, a survey was conducted among the Directors of the Italian HTCs. From questionnaires returned by 55% of them, data on the use of rFVIIa and APCC in children, adolescent, and adult patients with hemophilia A and inhibitors were obtained and are summarized in this article, including information about the implementation of prophylaxis with both bypassing agents, the adopted regimens, and reasons for starting, adjusting, and interrupting such a therapeutic approach.
Keywords: hemophilia A; inhibitors; prophylaxis; bypassing agents; activated prothrombin complex concentrate; recombinant activated factor VII